1994
DOI: 10.2307/3712173
|View full text |Cite
|
Sign up to set email alerts
|

Ways of Seeing Ecstasy in Modern Society: Experiential-Expressive and Cultural-Linguistic Views

Abstract: Religious experience is an important but understudied aspect of religion. Sociologists need a theoretical approach that appreciates the existence of and variation in the social distribution of reli~ous experiences. Recogni~ng that theories are interpretive frameworks through which we view the world, and understanding that "every way of seeing is a way of not seeing," use examine two potential "ways of seeing" religious experience in modern society and explore their ability to shed light upon recent surveys whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Previous research has indicated that worship service attendance, frequency of prayer, and biblical literalism are significant predictors of religious experiences (Baker, 2009;Hay and Morisy, 1978;Yamane and Polzer, 1994), and it follows that these forms of religious commitment should predict belief in angels as well. Service attendance and frequency of prayer are both commonly used by sociologists of religion as measures of religious devotion or practice, and the BRS contains a third item, frequency of reading sacred texts, that captures another aspect of individual religiosity.…”
Section: Religion and Paranormal Measuresmentioning
confidence: 98%
“…Previous research has indicated that worship service attendance, frequency of prayer, and biblical literalism are significant predictors of religious experiences (Baker, 2009;Hay and Morisy, 1978;Yamane and Polzer, 1994), and it follows that these forms of religious commitment should predict belief in angels as well. Service attendance and frequency of prayer are both commonly used by sociologists of religion as measures of religious devotion or practice, and the BRS contains a third item, frequency of reading sacred texts, that captures another aspect of individual religiosity.…”
Section: Religion and Paranormal Measuresmentioning
confidence: 98%
“…For example, Kirkpatrick's (1997) study found quali ed support for a relationship between attachment styles (e.g., commitment to relationships) and religiosity, the notion being that certain religious beliefs are tantamount to spiritual attachments that may compensate for the lack of certain social attachments. Yamane and Polzer (1994) focused on a more sociological aspect of religiosity: how religious traditions create alternative realities for adherents, which in turn facilitate ecstatic experiences with paranormal characteristics. MacDonald (1995) established an even stronger tie between religious and paranormal beliefs.…”
Section: Notesmentioning
confidence: 99%
“…The exponents of this paradigm endeavor to systematically apply economic market theory to religion (cf. Yamane and Polzer, 1994). They argue that, as in secular markets, people's choices of religious goods and services are guided by the economic principle of utility maximization (cf.…”
Section: Discussionmentioning
confidence: 99%